Spare Adenosine A2a Receptors Are Associated with Positive Exercise Stress Test in Coronary Artery Disease - Jean Ruf; Franck Paganelli; Laurent Bonello; Nathalie Kipson; Giovanna Mottola; Julien Fromonot; Jocelyne Condo; Alain Boussuges; Laurie Bruzzese; François Kerbaul; Yves Jammes; Vlad Gariboldi; et al. (BMC, 2016)
Abstract During exercise, cardiac oxygen consumption increases and the resulting low oxygen level in the myocardium triggers coronary vasodilation. This response to hypoxia is controlled notably by the vasodilator adenosine and its A2A receptor (A2AR). According to the "spare receptor" pharmacological model, a strong A2AR-mediated response can occur in the context of a large number of receptors remaining unoccupied, the activation of only a weak fraction of A2AR (evaluated using KD), which results in maximal cAMP production (evaluated using EC50), and hence in maximal coronary vasodilation. In coronary artery disease (CAD), myocardial ischemia limits adaptation to exercise, which is commonly detected using the exercise stress test (EST). We hypothesized that spare A2AR is present in CAD patients to correct ischemia. Seventeen patients with angiographically documented CAD and 17 control subjects were studied. We addressed adenosine-plasma concentration and A2AR-expression at the mononuclear cell-surface, which reflects cardiovascular expression. The presence of spare A2AR was tested using an innovative pharmacological approach based on a homemade monoclonal antibody with agonist properties. EST was positive in 82% of patients and in none of the controls. Adenosine plasma concentration increased by 60% at peak exercise in patients and in none of the controls (p < 0.01). Most patients (65%), and none of the controls, had spare A2AR (identified when EC50/KD ≤ 0.1) and a low A2AR-expression (mean: −37% versus controls; p < 0.01). All patients with spare A2AR had a positive EST whereas the subjects without spare A2AR had a negative EST (p < 0.05). Spare A2AR is therefore associated with positive EST in CAD patients and its detection may be used as a diagnostic marker.